2008
DOI: 10.1161/strokeaha.107.509158
|View full text |Cite
|
Sign up to set email alerts
|

Cellular NAD Replenishment Confers Marked Neuroprotection Against Ischemic Cell Death

Abstract: Background and Purpose-NADϩ is an essential cofactor for cellular energy production and participates in various signaling pathways that have an impact on cell survival. After cerebral ischemia, oxidative DNA lesions accumulate in neurons because of increased attacks by ROS and diminished DNA repair activity, leading to PARP-1 activation, NAD

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
103
2
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(115 citation statements)
references
References 26 publications
7
103
2
3
Order By: Relevance
“…This protection was not dependent on rCBF changes, as wild-type and fat-1 mice demonstrated equivalent rCBF changes ( Fig. 1F-H ), which were measured by IAP autoradiography 15 min after the onset of MCAO (Sawada et al, 2000;Stetler et al, 2008). These data strongly indicate that n-3 PUFAs alleviate acute brain injury induced by focal ischemia in mice.…”
Section: N-3 Pufas Alleviate Acute Brain Injury Induced By Focal Ischmentioning
confidence: 65%
See 2 more Smart Citations
“…This protection was not dependent on rCBF changes, as wild-type and fat-1 mice demonstrated equivalent rCBF changes ( Fig. 1F-H ), which were measured by IAP autoradiography 15 min after the onset of MCAO (Sawada et al, 2000;Stetler et al, 2008). These data strongly indicate that n-3 PUFAs alleviate acute brain injury induced by focal ischemia in mice.…”
Section: N-3 Pufas Alleviate Acute Brain Injury Induced By Focal Ischmentioning
confidence: 65%
“…For the long-term studies (21 d), the corner test and rotarod test (IITC Life Science) were performed up to 7 d after MCAO. The Morris water maze test was performed from day 15 to day 21 following MCAO by a blinded observer to evaluate cognitive function (Stetler et al, 2008). Following this test, animals were killed by perfusion and the brain sections (5 m) were stained with antimicrotubule-associated protein 2 (MAP2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that, by supplying NAD + precursors or intermediates and/or introducing PARPs or CD38 inhibitor, one could enhance the NAD + biosynthesis and/or inhibit its consumption, thus boosting the intracellular NAD + level (6,10,11,43). Such interventions are suggested to promote therapeutic effects of lifespan extension and neuroprotection and could potentially be used with other physiological managements, such as calorie restriction, fasting, or exercise, to compensate for the natural decline of brain NAD + in normal aging and prevent or treat age-related metabolic disorders (3,4,33,44,45).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, after several protein families associated with cell survival were found to use NAD + as their main substrate with activities also regulated by the availability of the NAD + , the full extent of the NAD's function as a metabolic regulator began to unfold (3)(4)(5). A growing number of studies have indicated that NAD + can modulate metabolic signaling pathways and mediate important cellular processes, including calcium homeostasis, gene expression, aging, degeneration, and cell death; therefore, the cellular NAD could serve as a therapeutic target for treating various metabolic or age-related diseases and promoting longevity (6)(7)(8)(9)(10)(11)(12).…”
mentioning
confidence: 99%